†Propercarina occidentalis, sp. nov., a new percomorph from the Oligocene of the Unterfeld (“Frauenweiler”) clay pit, and its relationships to Stromateoidei - Norbert Micklich; Tomáš Přikryl (PalZ, 2025)

The biodiversity of the Eocene Messel Pit - Krister T. Smith; Margaret Collinson; Annelise Folie; Jörg Habersetzer; Florian Hennicke; Erika Kothe; Thomas Lehmann; Olaf K. Lenz; Gerald Mayr; Norbert Micklich; Renate Rabenstein; Rachel Racicot; et al. (Palaeobiodiversity and Palaeoenvironments, 2024)
The Messel Pit is a Konservat-Lagerstätte in Germany, representing the deposits of a latest early to earliest middle Eocene maar lake, and one of the first palaeontological sites to be included on the list of UNESCO World Heritage Sites. One aspect of Messel that makes it so extraordinary is that its sediments are rich in different fossilised organisms – microfossils, plants, fungi, invertebrate animals and vertebrates – that are rarely preserved together. We present an updated list of all taxa, named or not, that have been documented at Messel, comprising 1409 taxa, which represent a smaller but inexactly known number of biological species. The taxonomic list of Labandeira and Dunne (2014) contains serious deficiencies and should not be used uncritically. Furthermore, we compiled specimen lists of all Messel amphibians, reptiles and mammals known to us. In all, our analyses incorporate data from 32 public collections and some 20 private collections. We apply modern biodiversity-theoretic techniques to ascertain how species richness tracks sampling, to estimate what is the minimum asymptotic species richness, and to project how long it will take to sample a given proportion of that minimum richness. Plant and insect diversity is currently less well investigated than vertebrate diversity. Completeness of sampling in aquatic and semiaquatic, followed by volant, vertebrates is higher than in terrestrial vertebrates. Current excavation rates are one-half to two-thirds lower than in the recent past, leading to much higher estimates of the future excavation effort required to sample species richness more completely, should these rates be maintained. Species richness at Messel, which represents a lake within a paratropical forest near the end of the Early Eocene Climate Optimum, was generally higher than in comparable parts of Central Europe today but lower than in present-day Neotropical biotopes. There is no evidence that the Eocene Messel ecosystem was a “tropical rainforest.”

Oechsleria unterfeldensis, gen. et sp. nov., a sailfin velifer fish (Lampridiformes, Veliferidae) from the Oligocene of the Unterfeld (“Frauenweiler”) clay pit - Norbert Micklich; Alexandre F. Bannikov (PalZ, 2023)
These are the first and so far only records of a sailfin velifer fish from the Lower Oligocene of the Unterfeld (“Frauenweiler”) clay pit at Rauenberg (S Germany), and only the fourth fossil skeletal finds of this group worldwide. The new genus and species † Oechsleria unterfeldensis is described in detail, diagnosed, and compared to other fossil and extant representatives of the Veliferidae. It appears to be a comparatively small-sized fish, which differs from the other representatives of this family, apart from body proportions, by having a lower number of vertebrae and dorsal-fin rays, the absence of massive spines in the dorsal and anal fins, four anal-fin pterygiophores in front of the anteriormost haemal spine, and a different morphology and size of various skeletal elements. Amongst others, the following character states are of relevance: a supraoccipital that is laterally sculptured by strong surface ridges; a weak ascending process of the premaxilla that is shorter than in the other veliferid taxa; compound (fused) anteriormost dorsal- and anal-fin pterygiophores, together with spineless dorsal and anal fins with unornamented rays (no spinules), of which the majority are bilaterally paired and both halves are fused only proximally but separate and segmented distally; a short coracoid that does not reach the ventral body margin; a broad and anterodorsally directed pelvic bone that bears a well-developed postpelvic process, and probably also the presence of a short pointed neural spine (in contrast to a distally blunt one and/or a low crest) on the second preural centrum. All in all, the new fossil records remarkably increase the known biodiversity of the Veliferidae. They also expand the known palaeogeographic range of this family as far as to the Western Paratethys. With reference to the occurrence and life habits as deduced from the extant forms, they seem to be another Indo-Pacific (respectively Palaeo-Mediterranean, when referring to the fossil forms) element of the Grube Unterfeld fish fauna with a preference for deeper waters and affinities to temperate to tropical climates.

First record of ponyfishes (Perciformes: Leiognathidae) from the Oligocene of the Grube Unterfeld (“Frauenweiler”) clay pit - Norbert Micklich; Alexandre F. Bannikov; Yoshitaka Yabumoto (PalZ, 2017)

Erratum to: Oligoremora rhenana n. g. n. sp., a new echeneid fish (Percomorpha, Echeneoidei) from the Oligocene of the Grube Unterfeld (“Frauenweiler”) clay pit - Norbert Micklich; Růžena Gregorová; Alexandre F. Bannikov; Dorin-Sorin Baciu; Ionuţ Grădianu; Giorgio Carnevale (PalZ, 2016)

Oligoremora rhenana n. g. n. sp., a new echeneid fish (Percomorpha, Echeneoidei) from the Oligocene of the Grube Unterfeld (“Frauenweiler”) clay pit - Norbert Micklich; Růžena Gregorová; Alexandre F. Bannikov; Dorin-Sorin Baciu; Ionuţ Grădianu; Giorgio Carnevale (PalZ, 2016)

Peculiarities of the Messel fish fauna and their palaeoecological implications: a case study - Norbert Micklich (Palaeobiodiversity and Palaeoenvironments, 2012)

New specimens of the avian taxa Eurotrochilus (Trochilidae) and Palaeotodus (Todidae) from the early Oligocene of Germany - Gerald Mayr; Norbert Micklich (PalZ, 2010)

First fossil records of the tholichthys larval stage of butterfly fishes (Perciformes, Chaetodontidae), from the Oligocene of Europe - Norbert Richard Micklich; James C. Tyler; G. David Johnson; Ewa Świdnicka; Alexandre F. Bannikov (PalZ, 2009)

Wolfsbarsch-Funde (Perciformes, Moronidae) aus den Süßwasser-Diatomiten von Kučlín (Böhmen) nebst Anmerkungen zur taxonomischen Stellung von„Perca“ lepidota aus den Süßwasser-Kalken von Öhningen (Baden) - Norbert Micklich; Madelaine Böhme (PalZ, 1997)